Chemical Solution Deposition of Epitaxial Metal‐Oxide Nanocomposite Thin Films. Issue 1 (6th February 2013) - Fei, Ling; Naeemi, Maitham; Zou, Guifu; Luo, Hongmei
ABSTRACT: Epitaixial metal‐oxide nanocomposite films, which possess interesting multifunctionality, have found applications in a wide range of devices. However, such films are typically produced by using high‐vacuum equipment, like pulse‐laser deposition, molecular‐beam epitaxy, and chemical vapor deposition. As an alternative approach, chemical solution methods are not only cost‐effective but also offer several advantages, including large surface coating, good control over stoichiometry, and the possible use of dopants. Therefore, in this Personal Account, we review the chemistry behind several of the main solution‐based approaches, that is, sol‐gel techniques, metal‐organic decomposition, chelation, polymer‐assisted deposition, and hydrothermal methods, including the seminal works that have been reported so far, to demonstrate the advantages and disadvantages of these different routes.